If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x+8)=(3x+2)
We move all terms to the left:
(5x+8)-((3x+2))=0
We get rid of parentheses
5x-((3x+2))+8=0
We calculate terms in parentheses: -((3x+2)), so:We get rid of parentheses
(3x+2)
We get rid of parentheses
3x+2
Back to the equation:
-(3x+2)
5x-3x-2+8=0
We add all the numbers together, and all the variables
2x+6=0
We move all terms containing x to the left, all other terms to the right
2x=-6
x=-6/2
x=-3
| -5(1-5x)+5(-8x–2)=-4x–8x | | -4(x–5)=44 | | 1,000x=0.001 | | 2x-4x=13 | | 3n+5=29-5n | | -x–3=4 | | 38=24-8a | | 1/2(6x-12)=18-2x | | K^2-10k=-16 | | 5(x+3)=19 | | x+7.1=3.0 | | 8x-3-(5-2x)=4,3 | | X+12/3=2x+3/x+2 | | X^2-6x+272=0 | | -12=w-3 | | 4−2x=−x+5 | | 4−2x=−x+5. | | 8x–3-(5-2x)=4,3 | | 5x-+3=19 | | 8x–3–(5–2x)=4,3 | | 8x–3–(5–2x)=4.3 | | 8x–3–(5–2x)=4,3; | | Y=3x/(x^2-9) | | Y+5=2x+2 | | 3(x+8)=6-2x | | -18-12x=-4-5x | | 7x-84+3x=180 | | 6x+3.1=6x-5.3 | | 3x+7x-84=180 | | 6*2^x=36 | | X^2=-10+3x | | 3x^2-11/x^2+3x=3 |